Characteristics of carbohydrate counting practice associated with adequacy of glycated hemoglobin in adults with type 1 diabetes mellitus in Brazil - Uliana, Gabriela Correia; Camara, Lediane Nunes; Paracampo, Carla Cristina Paiva; da Costa, Juliana Carvalho; Gomes, Daniela Lopes (Frontiers in Endocrinology, 2023)
Background: The Carbohydrate Counting (CC) is directly associated with achieving glycemic control by people with Type 1 Diabetes Mellitus (T1DM). Therefore, this study aims to analyze characteristics of the CC practice associated with the adequacy of glycated hemoglobin (HbA1c) in adults with T1DM in Brazil. Methods: The study was cross-sectional, carried out using an online form with questions about knowledge of CC, clinical, anthropometric, sociodemographic data, follow-up with health professionals and understanding of the concepts of CC. Pearson's chi-square test and binomial logistic regression analysis (p<0.05) were applied. Results: 173 adults participated, of which 57.2% had increased HbA1c (≥7%). Having the diabetes duration <10 years (p=0.006), performing the CC at lunch (p=0.040) and dinner (p=0.018), using specific applications to perform the CC (p=0.001), having learned to perform CC with a nutritionist (p=0.037) and knowing how to correctly define the concepts of food bolus (p=0.001), correction bolus (p<0.001) and insulin/carbohydrate ratio (p<0.001) was associated with having adequate HbA1c (<7%). Participants who were undergoing CC practice were 3.273 times more likely to have adequate HbA1c and participants with diabetes duration <10 years were 2.686 times more likely to have adequate HbA1c. Conclusion: It was concluded that variables transversal to CC favor adequate HbA1c values in adults with T1DM and that practicing CC and having a diabetes duration of less than 10 years are predictive factors of having adequate HbA1c.